Assessment of damages on a RC building after a big fire - Ada, Mehmet; Sevim, Barb; Yuzer, Nabi; Ayvaz, Yusuf (TECHNO-PRESS, 2018)
This paper presents a case study about the damages on the structural elements of a cast in place reinforced concrete (RC) building after a big fire which was able to be controlled after six hours. The fire broke off at the 2nd basement floor of the building, which has five basements, one ground, and two normal floors. As a result of intensely stocked ignitable materials, it spread out to the all of the upstairs. In visual inspection, most of the typical fire damages were observed (such as spalling, net-like cracks, crumbled plasters, bared or visible reinforcement). Also, failures of the 2nd basement columns were encountered. It has been concluded that the severity failures of the columns at the 2nd basement caused utterly deformation of the building, which is responsible for the massive damages on the beam-column connections. All of the observed damages were categorized related to the types and presented separated regarding the floors. Besides to the visual inspection, the numerical analysis was run to verify the observed damaged on the building for columns, beams, and the connection regions. It is concluded from the study that several parameters such as duration of the fire, level of the temperature influence on the damages to the RC building. Also, it is highlighted by the study that if the damaged building is considered on the overall structural system, it is not able to satisfy the minimum service requirements neither gravity loads nor earthquake conditions.
Keywords: beam-column connection damage; elevated temperature; fire damage; RC building; structural element; HIGH-STRENGTH CONCRETE; HIGH-TEMPERATURES; SAFETY DESIGN; PERFORMANCE; EXPOSURE; BOND; Construction & Building Technology; Engineering; Materials Science